I assume that you want to write \(y\) in terms of \(a, b, c\). Since \(\log_m{\frac{p}{q}} = \log_m{p}-\log_m{q}\), you will get that \[\log_m{y} = \log_m{\frac{\frac{a}{b}}{c}} = \log_m{\frac{a}{bc}}\Rightarrow y = \frac{a}{bc}\]
–
Kay Xspre
·
10 months, 2 weeks ago

## Comments

Sort by:

TopNewestI assume that you want to write \(y\) in terms of \(a, b, c\). Since \(\log_m{\frac{p}{q}} = \log_m{p}-\log_m{q}\), you will get that \[\log_m{y} = \log_m{\frac{\frac{a}{b}}{c}} = \log_m{\frac{a}{bc}}\Rightarrow y = \frac{a}{bc}\] – Kay Xspre · 10 months, 2 weeks ago

Log in to reply

– Cedie Camomot · 10 months, 2 weeks ago

Ohh we are the same of taught thanks?Log in to reply